Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2009
DOI: 10.1145/1518701.1519004
|View full text |Cite
|
Sign up to set email alerts
|

"When I am on Wi-Fi, I am fearless"

Abstract: Increasingly, users access online services such as email, ecommerce, and social networking sites via 802.11-based wireless networks. As they do so, they expose a range of personal information such as their names, email addresses, and ZIP codes to anyone within broadcast range of the network. This paper presents results from an exploratory study that examined how users from the general public understand Wi-Fi, what their concerns are related to Wi-Fi use, and which practices they follow to counter perceived thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(19 citation statements)
references
References 18 publications
2
12
0
1
Order By: Relevance
“…Dourish et al [23] when looking at how people went about managing digital privacy in the workplace found that people were employing "subtle practices to achieve privacy and security goals, such as positioning a computer screen such that visitors in an office could not see it, or stacking papers according to a secret rationale." In another related study Klasnja et al [44] focused upon how people tried to preserve their privacy when using devices in public places and observed that they were using strategies such as "tilting or dimming the screen, or finding a seat against the wall". In the studies being drawn upon here there was a range of similar phenomena, with various kinds of concerns about visibility being articulated.…”
Section: Keeping Things From Viewmentioning
confidence: 99%
“…Dourish et al [23] when looking at how people went about managing digital privacy in the workplace found that people were employing "subtle practices to achieve privacy and security goals, such as positioning a computer screen such that visitors in an office could not see it, or stacking papers according to a secret rationale." In another related study Klasnja et al [44] focused upon how people tried to preserve their privacy when using devices in public places and observed that they were using strategies such as "tilting or dimming the screen, or finding a seat against the wall". In the studies being drawn upon here there was a range of similar phenomena, with various kinds of concerns about visibility being articulated.…”
Section: Keeping Things From Viewmentioning
confidence: 99%
“…Unlike most other smart home devices, which are typically bought for their "smarts", a consumer might well purchase a smart TV without wanting or even knowing about those features, simply because most models now on the market have them. So users may be unaware of what data is being collected and what's being sent to various servers; after all, few users are even aware of how data flows when on Wi-Fi [29].…”
Section: Introductionmentioning
confidence: 99%
“…Other examples of assessing people's awareness of privacy risks are interviews conducted by Friedman et al [24], who found that people were concerned about risks to their information and especially their privacy, but did not further specify these privacy risks, a survey on security and privacy risks of eHealth wearables [25], interviews combined with a field study concerning the risks of WiFi use [26], a comprehensive study on user regrets regarding Facebook posts [27], a survey assessing perceived risks of using mobile devices to conduct online transactions [28], and surveys and interviews concerning risks of cloud storage [29]. Shirazi and Volkamer [30] conducted interviews with 20 people on identification and tracking on the web, and found that their participants most often mentioned personalized advertising as a possible consequence, which some of them even considered to be beneficial.…”
Section: A Mental Models Of Privacy Consequencesmentioning
confidence: 99%